Patient and caregiver perspectives on decision support for symptom and quality of life management during cancer treatment: Implications for eHealth. Issue 8 (3rd July 2017) - Cooley, Mary E.; Nayak, Manan M.; Abrahm, Janet L.; Braun, Ilana M.; Rabin, Michael S.; Brzozowski, Jane; Lathan, Christopher; Berry, Donna L.
Abstract: Objectives: Adequate symptom and quality‐of‐life (SQL) management is a priority during cancer treatment. eHealth is a timely way to enhance patient‐engagement, facilitate communication, and improve health outcomes. The objectives of this study were to describe patient and caregivers' perspectives for providing, processing, and managing SQL data to enhance communication and identify desired components for decision support. Methods: Data were collected from 64 participants through questionnaires and focus groups. Analysis was conducted using NVivo. Open and axial coding was completed, grouping commonalities and large constructs into nodes to identify and synthesize themes. Results: Face‐to‐face meetings with clinicians were the prime time to communicate, and patients strove to understand treatment options and the effect on SQL by bringing caregivers to their visits, taking notes, tracking symptoms, and creating portable health records. Patients/caregivers struggled to self‐manage their symptoms and were uncertain when to contact clinicians when experiencing uncontrolled symptoms. Most participants identified eHealth solutions for decision support. However, 38% of participants (n = 24) rarely used computers and identified non‐eHealth options for decision support. Core components for both eHealth and non‐eHealth systems were access to (1) cancer information, (2) medical records, (3) peer support, and (4) improved support and understanding on when to contact clinicians. Conclusions: Patients were faced with an overwhelming amount of information and relied on their caregivers to help navigate the complexities of cancer care and self‐manage SQL. Health technologies can provide informational support; however, decision support needs to span multiple venues to avoid increasing disparities caused by a digital divide.